Protecting Children's Rights in Civil, Criminal and International Law – Under a Touch of Digitalization - Mensah, Cocou Marius (2024)
The publication focuses on the crucial topics of protecting children's rights in civil, criminal, and international law. In today's rapidly evolving digital landscape, ensuring the well-being and rights of children has become more complex yet paramount. This comprehensive exploration delves into the multifaceted legal frameworks and challenges surrounding children's rights in various legal domains. From issues of custody and education to juvenile justice and international treaties, this book offers insights into the evolving landscape of child protection laws. With a keen focus on navigating the digital age's influence on children's rights, this publication serves as a valuable resource for legal professionals, policymakers, educators, and advocates dedicated to safeguarding the rights and welfare of children.
Keywords: children's rights; national and international legal frameworks; family relationships; measures for the protection of children's rights; gatekeeping; digital environment